ANALYSIS OF THE ROLE AND SPECIAL FEATURES OF THE RESTAURANT BUSINESS IN THE DEVELOPMENT OF THE SERVICE INDUSTRY IN BUKHARA REGION (Scientific Journal of Actuarial Finance and Accounting, 2024)
This article provides practical information on the analysis of the role and special features of the restaurant business in the development of the service sector in the Bukhara region.